Microstructure evolution, mechanism of electric breakdown strength, and dielectric energy storage performance of CuO modified Ba0.65Sr0.245Bi0.07TiO3 Pb-free bulk ceramics. Issue 17 (1st December 2019) - Liu, Gang; Li, Yang; Dong, Jia; Yu, Linjiang; Zhang, Yutong; Hu, Jinzhu; Gao, Jinghui; He, Zhanbing
Abstract: Barium titanate (BaTiO3 )-based lead-free relaxor ferroelectric ceramic Ba0.65 Sr0.245 Bi0.07 TiO3 was developed via a traditional electrocremic processing technique to obtain Pb-free dielectric bulk ceramics with enhanced energy storage performance that can be potentially used in pulsed power devices. The added CuO can broaden the phase transition peak, and move it to lower temperature, reinforcing the dielectric relaxor behavior. The microstructure evolution of the sample was investigated via Piezoforce microscopy, and the corresponding mechanism regarding the electric breakdown strength was studied. The solubility of solid CuO in the Ba0.65 Sr0.245 Bi0.07 TiO3 is approximately 0.02 mol. The ceramic sample with 0.005 mol CuO possesses 160 kV/cm electrical breakdown strength and an energy storage efficiency higher than 76%, which yields 1.28 J/cm 3 energy storage density. Moreover, the ceramic specimen with 0.005 CuO exhibits relatively good temperature stability, good frequency stability from 1 Hz to 200 Hz, and also good fatigue resistance up to 10 5 cycles, and can be a potential candidate for future energy storage applications.